An Assessment of Probability Encoding Using a Probabilistic, Noninteractive Management Game - McDevitt, Carl D.; Watson, Hugh J. (Academy of Management Journal, 1978)
This study illustrates the usefulness of a probabilistic, noninteractive management game as a research instrument. Employing an inventory-control game, it was found that practicing managers are capable of internalizing the parameters of underlying distributions as increasing amounts of information become available. Encoding method was found to impact response accuracy, and systematic alteration of responses improved accuracy.